Successful long-term management for postoperative sternal infection with multiple disseminated lymphadenitis caused by Mycobacterium abscessus - Takahiro Yanagihara; Tomoyuki Kawamura; Kenji Minagi; Yasuharu Sekine; Kazuto Sugai; Hideo Ichimura; Yukio Sato (Surgical Case Reports)
Abstract Background Postoperative sternal infection caused by Mycobacterium abscessus (M. abscessus) is rare, but associated with a high 2-year mortality rate of 40%. Decision-making around treatment strategy is challenging. Here, we present a successfully treated case of postoperative M. abscessus sternal infection with multiple disseminated lymphadenitis. Case presentation The patient, an 80-year-old woman with anterior mediastinal tumor and myasthenia gravis, underwent extended thymectomy under median sternotomy. Redness appeared around the scar two months after the operation. Sternal wires were removed, debridement was performed, and the wound was kept open. Mycobacterium abscessus was isolated from the wound culture. The disseminated lesions in the right axillary, parasternal, and bilateral supraclavicular lymph nodes, rendered surgical options for infection control difficult; therefore, she was treated conservatively with antibiotics and negative pressure wound therapy (NPWT). The wound diminished but infectious granulation tissue remained after NPWT. Two disseminated lesions were percutaneously punctured and drained of pus, which resulted in negative cultures. Additional debridement and wound closure were performed. She was discharged after switching to oral antibiotics. No recurrence was observed five months after the antibiotics were completed (total sensitive antibiotics use: 366 days). Conclusions Repeated culture assessment of disseminated lesions is recommended to facilitate the development of appropriate therapeutic strategies. Localized procedures may be an option for patients with controlled disseminated lesions evidenced by negative cultures.